2015
DOI: 10.1002/btpr.2172
|View full text |Cite
|
Sign up to set email alerts
|

Binding domains of Bacillus anthracis phage endolysins recognize cell culture age‐related features on the bacterial surface

Abstract: Bacteriolytic enzymes often possess a C-terminal binding domain that recognizes specific motifs on the bacterial surface and a catalytic domain that cleaves covalent linkages within the cell wall peptidoglycan. PlyPH, one such lytic enzyme of bacteriophage origin, has been reported to be highly effective against Bacillus anthracis, and can kill up to 99.99% of the viable bacteria. The bactericidal activity of this enzyme, however, appears to be strongly dependent on the age of the bacterial culture. Although h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Given the complexity of the cell wall, it is possible that the cell wall substrate for CD11 may not be easily accessible in metabolically competent cells in growth medium. To test this hypothesis, a pull-down assay was performed with the bound enzyme detected by SDS-PAGE 33 34 ; this assay was facilitated by the solubility of CD11 in the conditions tested ( Supplementary Fig. S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Given the complexity of the cell wall, it is possible that the cell wall substrate for CD11 may not be easily accessible in metabolically competent cells in growth medium. To test this hypothesis, a pull-down assay was performed with the bound enzyme detected by SDS-PAGE 33 34 ; this assay was facilitated by the solubility of CD11 in the conditions tested ( Supplementary Fig. S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to changes in the cell wall structure that render the binding ligand more available, or to a more prevalent expression of the ligand in the stationary phase. It has recently been reported that the CBDs of Bacillus anthracis phage endolysins are able to recognize cell culture age‐related features on the bacterial surface (Paskaleva et al ., ). Boiling Clostridium cells also increased the binding efficiency of CTP1L and its CBD.…”
Section: Discussionmentioning
confidence: 97%